Time-dependent diffusion coefficient of proton in polymer electrolyte membrane - Ohkubo, Takahiro; Kidena, Koh; Ohira, Akihiro (Diffusion Fundamentals, 2009)
We investigated the time-dependent self-diffusion coefficients of water, D(T eff), in polymer electrolyte membranes at 278 K. TheD(T eff) was measured from T eff=0.7 to 100 ms by field gradient NMR techniques. The results showed that the self-diffusion coefficients of water were dependent on T eff less than 2 ms due to restricted diffusion, and were constant beyond 3 ms. The tortuosity and surface-to-volume ratio related to water diffusion were also estimated from D(T eff). The obtained values revealed the existence of large-scale restricted geometry compared with well-known nanometer-sized domain in polymer electrolyte membranes.